Drug survival on TNF inhibitors in patients with rheumatoid arthritis comparison of adalimumab, etanercept and infliximab. Issue 2 (27th November 2013) - Neovius, M; Arkema, E V; Olsson, H; Eriksson, J K; Kristensen, L E; Simard, J F; Askling, J
Abstract : Objective: To compare drug survival on adalimumab, etanercept and infliximab in patients with rheumatoid arthritis (RA). Methods: Patients with RA (n=9139; 76% women; mean age 56 years) starting their first tumour necrosis factor (TNF) inhibitor between 2003 and 2011 were identified in the Swedish Biologics Register (ARTIS). Data were collected through 31 December 2011. Drug survival over up to 5 years of follow-up was compared overall and by period of treatment start (2003–2005/2006–2009; n=3168/4184) with adjustment for age, sex, education, period, health assessment questionnaire (HAQ), disease duration, concomitant disease modifying antirheumatic drug (DMARD) treatment and general frailty (using hospitalisation history as proxy). Results: During 20 198 person-years (mean/median 2.2/1.7 years) of follow-up, 3782 patients discontinued their first biological (19/100 person-years; 51% due to inefficacy, 36% due to adverse events). Compared with etanercept, infliximab (adjusted HR 1.63, 95% CI 1.51 to 1.77) and adalimumab initiators had higher discontinuation rates (1.26, 95% CI 1.16 to 1.37), and infliximab had a higher discontinuation rate than adalimumab (1.28, 95% CI 1.18 to 1.40). These findings were consistent across periods, but were modified by time for adalimumab versus etanercept (p<0.001; between-drug difference highest the 1st year in both periods). The discontinuation rate was higher for starters in 2006–2009 than 2003–2005 (adjusted HR 1.12, 95% CI 1.04 to 1.20). The composition of 1-year discontinuations also changed from 2003–2005 vs 2006–2009: adverse events decreased from 45% to 35%, while inefficacy increased from 43% to 53% (p<0.001). Conclusions: Discontinuation rates were higher for infliximab compared with adalimumab and etanercept initiators, and for adalimumab versus etanercept during the 1st year. Discontinuation rates increased with calendar period, as did the percentage discontinuations due to inefficacy.